Implementasi grey relational analysis (gra) dan fuzzy weighted product (fwp) dalam fuzzy multi-attribut desicion making untuk penilaian kesejahteraan masyarakat di wilayah kabupaten nganjuk - Mufidah, Do'aul Isma (Maliki Interdisciplinary Journal, 2025)
Community welfare is an important aspect of a region's development. Nganjuk Regency, with a relatively low level of Regency Minimum Wage (UMK), faces challenges in improving community welfare. Therefore, this research aims to evaluate community welfare in the region using the Grey Relational Analysis (GRA) and Fuzzy Weighted Product (FWP) methods in the Fuzzy Multi-Attribute Decision Making (FMADM) approach. The GRA method is used to analyze the relationship between criteria in determining welfare levels, while the FWP method enables fuzzy logic-based weight calculations to handle data uncertainty. The data used in this research was obtained from the Nganjuk Badan Pusat Statistik (BPS), with several indicators such as health, education, social protection, and housing. The results of the analysis show that 2023 has the highest level of welfare compared to previous years. A comparison between the two methods shows that GRA is superior in systematically evaluating inter-criteria relationships, while FWP is more flexible in dealing with data uncertainty. Both methods provide consistent results in identifying the main factors that contribute to community welfare.This research is expected to provide insight for the local government in formulating more effective policies to improve community welfare in Kabupaten Nganjuk.